“Think Globally, Act Locally:” The State Transformation Approach in Governing Borderless Security Threats - Lidya Christin Sinaga (JAS (Journal of ASEAN Studies), 2016)
The nature of security issues has changed significantly in recent decades. They are no longer just about war, but have extended into complex and transnational security issues or so-called Non-Traditional Security (NTS). Shahar Hameiri and Lee Jones in their new book Governing Borderless Threats, argue therefore that the emergence of NTS issues requires new modes of governance, instead of a simple extension of the logic of war suggested by the Copenhagen School or new responses of post-national governance.